2017
DOI: 10.5114/amscd.2017.69379
|View full text |Cite
|
Sign up to set email alerts
|

The microbiology and clinical characteristics of bacterial and fungal meningitis in a Chinese hospital

Abstract: A b s t r a c t Introduction:The aim was to investigate the distribution, antibiotic resistance, initial clinical and laboratory characteristics of pathogens isolated from the cerebrospinal fluid samples (CSF). Material and methods: The CSF were subjected for identification. The minimum inhibitory concentrations (MICs) of antimicrobial agents were tested. The initial clinical and laboratory characteristics were collected. Results: The rate of positive yield of pathogen meningitis in our study was 8.16% . Among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Globally, different microorganisms such as bacteria, viruses, fungi and parasites can cause meningitis [ 82 , 83 ]. Bacterial meningitis occurs among all age groups, especially during childhood [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Globally, different microorganisms such as bacteria, viruses, fungi and parasites can cause meningitis [ 82 , 83 ]. Bacterial meningitis occurs among all age groups, especially during childhood [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are many efforts aiming to identify a useful marker for quick diagnosis, treatment and follow-up in the cases of severe infections and other diseases in clinical practice [2,4,6,13,[16][17][18][19][20]. In this study, we examined the possibility of using HCT-ALB as a marker to aid in the diagnosis of severe infections.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion criteria: All patients were adults. For the infected patient group (group 1), patients were selected based on the clinical diagnosis and positive culture results (including bacteria and fungi investigations [16] in blood, sputum, midstream urine, pleural effusion and secretions). For the non-infected patient group (group 2), patients were selected based on the review of medical notes and laboratory results by an investigator who found no evidence of infectious cause and the most likely diagnosis fell into ICD-10 non-communicable disease category.…”
Section: Subjects and Collection Of Datamentioning
confidence: 99%
“…However, the overuse of therapy accelerated the process of generating drug tolerance, leading to an obstacle for a favorable therapeutic outcome [ 28 ]. After pathogens, such as HPV and EBV, make contact with the drug many times, the sensitivity of tumor cells was reduced or even disappeared, resulting in the reduction or invalidation of the drug to the pathogens [ 2 , 29 ]. Drug resistance of tumor cells is the central barrier for the medical domain to treat laryngeal carcinoma, and continuous use of the drug often hinders treatment results [ 16 , 30 ].…”
Section: Introductionmentioning
confidence: 99%